2019
DOI: 10.1007/s11368-019-02455-8
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and sorption processes of polycyclic aromatic hydrocarbons (PAHs) to organic matter in soils amended by exogenous rich-carbon material

Abstract: Purpose The aim of the research was to assess the effect of biochar addition on aging, degradation, and sorption processes of polycyclic aromatic hydrocarbons (PAHs) to soil organic matter. The study was carried out as a sorption experiment in strictly controlled water and air conditions, which allowed for the accurate observation and prediction of PAH behavior in soils. Materials and methods Four soils were fortified with a PAH mixture (Fluorene-Flu, Anthracene-Ant, Phenanthrene-Phe, Pyrene-Pyr, Chrysene-Chry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Adsorbed nanoparticles may have formed clusters on the solid. Besides silver nanoparticles, biochar was also used in the removal of other contaminants, e.g., heavy metals [ 28 , 32 , 33 ], dyes [ 34 , 35 ], gold nanoparticles [ 10 ], antibiotics [ 36 , 37 ], and PAH [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adsorbed nanoparticles may have formed clusters on the solid. Besides silver nanoparticles, biochar was also used in the removal of other contaminants, e.g., heavy metals [ 28 , 32 , 33 ], dyes [ 34 , 35 ], gold nanoparticles [ 10 ], antibiotics [ 36 , 37 ], and PAH [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated that biochar amendment led to an increase in soil organic carbon in 2-5, 1-2, 0.25-1 and <0.25 mm aggregates for each nitrogen fertilizer treatment, and SOC in 2-5, 1-2, 0.25-1 and <0.25 mm aggregates increased with the increase in biochar application. This was because the organic carbon content of biochar used in this experiment was 537.97 g•kg −1 , being a carbon-rich exogenous organic matter, thus it could increase the soil microbial biomass and promote the formation of soil humus to contribute to the formation of organic macromolecules such as carbohydrates and aromatic hydrocarbons, thereby increasing the content of soil organic carbon and producing more cementing materials, finally resulting in the redistribution of microaggregates in the soil into large aggregates [28]. This was also the reason why the application of 10 t•ha −1 biochar in this study promoted the formation of soil large aggregates and thus improved the stability of soil aggregates.…”
Section: Effect Of Biochar and Nitrogen Fertilizer On Total Organic Cmentioning
confidence: 99%
“…Soil is a critical environment because different pollutants come from various human activities, such as agriculture, industry, mining and transports which can pollute the soil with many dangerous pollutants, one of them is polycyclic aromatic hydrocarbon compounds (PAHs) (Wang et al, 2018). Polycyclic aromatic hydrocarbons are specific persistent organic pollutants that stay for long periods in the environment (Ukalska-Jaruga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%